Zebrafish Methods and Protocols - Kawakami, Koichi; Patton, E. Elizabeth; Orger, Michael (Methods in Molecular Biology, 2016)
This second edition details new emerging areas of zebrafish research focusing on genetics and genomics, techniques for developing and analyzing zebrafish disease models, and methods for neuroscience. Zebrafish: Methods and Protocols, Second Edition guides readers through methods for mutagenesis and genome editing in zebrafish, applications of GFP-expressing transgenic fish, techniques for cancer models, imaging of infection and host-pathogen interactions, metabolism and transport of lipids, and the structure and function of neural circuits and their role in generating behavior. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical Zebrafish: Methods and Protocols, Second Edition is a useful complement to the first book for new and experienced zebrafish researcher alike.